2014
DOI: 10.1088/0953-8984/26/37/375601
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb interaction parameters in bcc iron: an LDA+DMFT study

Abstract: We study the influence of Coulomb interaction parameters on electronic structure and magnetic properties of paramagnetic bcc Fe by means of the local density approximation plus dynamical mean-field theory approach. We consider the local Coulomb interaction in the density-density form as well as in the form with spin rotational invariance approximated by averaging over all directions of the quantization axis. Our results indicate that the magnetic properties of bcc Fe are mainly affected by the Hund's rule coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 86 publications
(105 reference statements)
15
29
0
Order By: Relevance
“…A number of earlier DFT+DMFT works [25][26][27] chose the parameter U of about 2 eV. More recent direct calculations within the constrained local-density and random-phase (cRPA) approximations [28,29] predict the static value of the Slater parameter F U 0 = in the range between 3 and 4 eV, only about 10% of reduction of the ambientcondition value was obtained in cRPA calculations for the inner-core atomic volume [15]. The 30% increase of the value used in DFT+DMFT calculations with respect to the static cRPA value was suggested in [30] to effectively account for the frequency dependence of the Coulomb vertex.…”
Section: Methodsmentioning
confidence: 99%
“…A number of earlier DFT+DMFT works [25][26][27] chose the parameter U of about 2 eV. More recent direct calculations within the constrained local-density and random-phase (cRPA) approximations [28,29] predict the static value of the Slater parameter F U 0 = in the range between 3 and 4 eV, only about 10% of reduction of the ambientcondition value was obtained in cRPA calculations for the inner-core atomic volume [15]. The 30% increase of the value used in DFT+DMFT calculations with respect to the static cRPA value was suggested in [30] to effectively account for the frequency dependence of the Coulomb vertex.…”
Section: Methodsmentioning
confidence: 99%
“…Many-electron effects in iron are expected to arise due to the on-site Coulomb repulsion between rather localized 3d states hybridized with itinerant 4s bands. The typical width W of the iron 3d band is in the range of 5 to 6 eV for the ambient pressure; the estimated value of the local Coulomb interaction parameter U (Slater F 0 ) is in the range from 2.3 to 6 eV, in accordance with constrained local-density approximation [15,16,17] and constrained random-phase approximation [18,19] calculations (see Appendix A for a short overview of these methods). In spite of a large spread in the theoretical estimates of U , one may conclude that the ratio U/W in Fe is less than or equal to 1.…”
Section: Introductionmentioning
confidence: 65%
“…1(a) the evolution with temperature of the mean value of the magnitude of the local Fe moments, as they are a key ingredient in many magnetic theories and studies on Fe-based systems, both in historically pioneering studies [54][55][56] and in recent works (see, e.g., Refs. [3,5,[9][10][11][12][13][14]17,57,58]). …”
Section: A Average Local Magnetic Momentsmentioning
confidence: 99%
“…On the other hand, Igoshev et al performed LDA+DMFT calculations and found that m 2 z of bcc Fe decreased at high temperature [11]. Both the effective local moments and the obtained critical temperature of DMFT calculations depend heavily on the parameters U and J [13]. All DMFT calculations so far have been done assuming an ideal lattice, thus neglecting vibrationally induced disorder.…”
Section: A Average Local Magnetic Momentsmentioning
confidence: 99%
See 1 more Smart Citation